(untitled) (Journal of Economic Research & Business Administration, 2025)
The aim of this study is to examine the impact of total factor productivity (TFP) on corporate performance, considering the sustainability of the company, including its ESG (Environmental, Social, and Governance) indicators, which have a significant influence on TFP. In a global environment marked by uncertainty, companies with high ESG scores demonstrate greater adaptability and resource allocation efficiency, contributing to the growth of TFP. Based on a rich sample of Chinese listed companies from 2010 to 2023, this study constructs a multiple regression fixed-effects model and conducts an empirical study using panel data. At the same time, we use multiple methods for robustness testing to ensure the reliability of the research results. The findings indicate that ESG has a positive effect on TFP, with corporate sustainability playing a mediating role through innovation capabilities, operational resilience, organizational resilience, and financial flexibility. Furthermore, significant differences are observed in the impact of ESG between companies with high market concentration, capital-intensive industries, high-pollution industries, and others. The study emphasizes the need for companies to develop resilience and innovation capabilities to enhance productivity and sustainability. Key words: ESG, Corporate Resilience, Operational Resilience, Financial Flexibility, Total Factor Productivity.